1995
DOI: 10.1021/jm00007a014
|View full text |Cite
|
Sign up to set email alerts
|

Search for New Purine- and Ribose-Modified Adenosine Analogs as Selective Agonists and Antagonists at Adenosine Receptors

Abstract: The binding affinities at rat A1, A2a, and A3 adenosine receptors of a wide range of derivatives of adenosine have been determined. Sites of modification include the purine moiety (1-, 3-, and 7-deaza; halo, alkyne, and amino substitutions at the 2- and 8-positions; and N6-CH2-ring, -hydrazino, and -hydroxylamino) and the ribose moiety (2'-, 3'-, and 5'-deoxy; 2'- and 3'- O-methyl; 2'-deoxy 2'-fluoro; 6'-thio; 5'-uronamide; carbocyclic; 4'- or 3'-methyl; and inversion of configuration). (-)- and (+)-5'-Noraris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 94 publications
(116 citation statements)
references
References 50 publications
4
108
0
1
Order By: Relevance
“…As previously reported 14 and confirmed in this study, the SAR of adenosine agonists indicates that the ribose ring oxygen may be substituted with carbon; however, much affinity is lost. As with the N 6 -(3-iodobenzyl) aristeromycin derivative, 7b, simple carbocyclic substitution of the ribose moiety of otherwise potent N 6 -substituted adenosine agonists greatly diminishes affinity.…”
Section: Discussionsupporting
confidence: 89%
“…As previously reported 14 and confirmed in this study, the SAR of adenosine agonists indicates that the ribose ring oxygen may be substituted with carbon; however, much affinity is lost. As with the N 6 -(3-iodobenzyl) aristeromycin derivative, 7b, simple carbocyclic substitution of the ribose moiety of otherwise potent N 6 -substituted adenosine agonists greatly diminishes affinity.…”
Section: Discussionsupporting
confidence: 89%
“…Since CADO (26,27) is equipotent to NECA at A 1 receptors (9.3 vs. 6.3 nM) and less potent than NECA at A 2a (63 vs. 10 nM), A 2b (24 vs. 2.6 ÎźM), and A 3 (1890 vs. 113 nM) receptors, it is likely that the mechanism of apoptosis induced by CADO is not via adenosine receptors. Tanaka et al (4) observed an effect of ADO but not CADO on polyADP ribosylation activity in HL-60 cells, further supporting distinct mechanisms for cell death induced by these two analogues.…”
Section: Resultsmentioning
confidence: 99%
“…The hypothesis of a non-A 1 /A 2 receptor-mediated pathway for the action of CADO is further supported by our finding that an ADO A 1 /A 2 antagonist XAC had no effect on CADO-induced apoptosis in HL-60 cells. It is also noteworthy that a closely related compound, 2-chloro-2′-deoxyadenosine (cladribine), also induces apoptosis in leukemic cells (28), probably in an ADO receptor-independent fashion since it binds only very weakly to the receptors (26). Cladribine is currently being used in the treatment of leukemia (21).…”
Section: Resultsmentioning
confidence: 99%
“…In an initial attempt, a large number of heterocyclic compounds were synthesized and evaluated as A 3 AR antagonists Siddiqi et al, 1995;Ji et al, 1996). In particular a triazoloquinazoline derivative 9-chloro-2-(2-furanyl)-5- [(phenylacetyl) (Kim et al, 1996).…”
Section: B Antagonistsmentioning
confidence: 99%